Paraplegia after Gastrectomy in a Patient with Cervical Disc Herniation: A Case Report and Review of Literature - Qingfu Zhang; Wei Jiang; Quanhong Zhou; Guangyan Wang; Linlin Zhao (Case Reports in Anesthesiology)
Paraplegia is a rare postoperative complication. We present a case of acute paraplegia after elective gastrectomy surgery because of cervical disc herniation. The 73-year-old man has the medical history of cervical spondylitis with only symptom of temporary pain in neck and shoulder. Although the patient’s neck was cautiously preserved by using the Discopo, an acute paraplegia emerged at about 10 hours after the operation. Severe compression of the spinal cord by herniation of the C4-C5 cervical disc was diagnosed and emergency surgical decompression was performed immediately. Unfortunately the patient showed limited improvement in neurologic deficits even after 11 months.